Skin diseases of the great folds. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2004)
This chapter faces the skin diseases affecting the axillary, inguinal and neck folds, that is the joint folds between the trunk, limbs and head. The neck is a true fold especially in the first months of life, when the disorders affecting the axillary and inguinal folds often involve even the neck. However, even later some skin diseases, such as acanthosis nigricans and pseudoxanthoma elasticum, affects both the axillary folds and the neck. These folds share some physiological characteristics such as the increased mobility, which explains the increased tendency to ulcerate of hemangioma in these sites, the increased temperature and, finally, the increased humidity leading to dilution of the defensive factors of the skin and increased pH. These physiological characteristics are magnified in the first years in the developed countries by the use of the disposable diaper, aimed at containing urine and feces. The external layer of the disposable diaper indeed increases by itself temperature and humidity in the involved area. The vasodilation caused by the increased temperature makes the diaper area a localization factor for many skin disorders, from psoriasis to Langerhans cell histiocytosis.